Joint Statement of Ministers - On the occasion of the Second Arctic Science Ministerial (2018)
We, the Ministers representing the eight Arctic States (Canada, the Kingdom of Denmark - here represented by Ministers of Denmark, Faroe Islands and Greenland -, Finland, Iceland, Norway, Russia, Sweden and the United States), fifteen further States (Austria, Belgium, China, France, Germany, Italy, Japan, Republic of Korea, the Netherlands, Poland, Portugal, Singapore, Spain, Switzerland, the United Kingdom), and the representative of the European Union, joined by representatives of six Arctic Indigenous Peoples Organizations (Aleut International Association, Arctic Athabaskan Council, Gwich'in Council International, Inuit Circumpolar Council, Russian Association of Indigenous Peoples of the North, Saami Council), have gathered to further enhance collaborative science efforts in the Arctic